2013
DOI: 10.1089/gtmb.2012.0461
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the PDCD6 Gene Are Associated with Increased Uterine Leiomyoma Risk in the Chinese

Abstract: Programmed cell death 6 (PDCD6) participates in T cell receptor, Fas, and glucocorticoid-induced programmed cell death. To test the relationship between PDCD6 polymorphisms and uterine leiomyomas (UL) risk, we investigated the association of two SNPs (rs4957014 and rs3756712) in PDCD6 with UL risk in a case-control study of 295 unrelated premenopausal UL patients and 436 healthy postmenopausal control subjects in a population of China. Genotypes of the two SNPs were determined with the use of PCR-restriction f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Two proteins from mEVs were predicted as potential surface markers of BC: programmed cell death protein 6 (PDCD6P) and small subunit processome component 20 (UTP20). PDCD6 is a pro-apoptotic protein contributing to T-cell receptor-, Fas-, and glucocorticoid-induced programmed cell death [76,77] as well as endoplasmic reticulum stress-induced apoptosis during organ formation [78,79]. PDCD6 expression was found to be upregulated in tumor tissue samples from lung, breast, colon, and ovarian cancers, which suggested that it may be involved in the maintenance of cellular viability [80][81][82].…”
Section: Discussionmentioning
confidence: 99%
“…Two proteins from mEVs were predicted as potential surface markers of BC: programmed cell death protein 6 (PDCD6P) and small subunit processome component 20 (UTP20). PDCD6 is a pro-apoptotic protein contributing to T-cell receptor-, Fas-, and glucocorticoid-induced programmed cell death [76,77] as well as endoplasmic reticulum stress-induced apoptosis during organ formation [78,79]. PDCD6 expression was found to be upregulated in tumor tissue samples from lung, breast, colon, and ovarian cancers, which suggested that it may be involved in the maintenance of cellular viability [80][81][82].…”
Section: Discussionmentioning
confidence: 99%
“…PDCD6 is a calcium-binding modulator associated with cell proliferation and death (38). Numerous studies have revealed that PDCD6 is associated with tumors; however, the underlying mechanism remains unclear (39)(40)(41)(42). Furthermore, one study demonstrated that overexpression of PDCD6 suppressed angiogenesis in vitro via the phosphatidylinositol 3-kinase/protein kinase mTOR/ribosomal protein S6 kinase B1 pathway (43).…”
Section: Discussionmentioning
confidence: 99%
“…However, PDCD6-deficient cells were no longer capable of blocking apoptosis induced by TCR, FAS, or dexamethasone signals 29. The expression levels and genotypes30 of PDCD6 are associated with cancer risk. In 2003, it was found that PDCD6 was upregulated at tumor sites relative to non-tumor sites among lung cancer patients 31.…”
Section: Introductionmentioning
confidence: 99%